Green Coffee Sourcing Methods and Customer Behaviour - Komár, Daniel (2022)
The coffee business has changed significantly over the past few years. Similarly to other branches, an increasing number of customers care more about the product they purchase, not only regarding quality but also ethical and environmental aspects. In the case of the coffee industry, this transformation is very significant. The proof for this claim is all those so-called specialty coffee roasteries and cafés that are being opened in large numbers worldwide. As it follows from the word ‘specialty’, these specialty roasteries should provide a special customer experience that requires high quality and wholesome primary product, in this case, green coffee beans. Since there are different options for green coffee sourcing, finding out how the choice of green coffee sourcing method influences customer behaviour will be the main task of this thesis. The secondary goal of this thesis will focus on the opposite part of the coffee supply chain, which is represented by green coffee producers (farmers). The aim is to evaluate the impact of different sourcing methods on their livelihoods. To accomplish these goals, two-level research was held for which primary data, quantitative for the main and qualitative for the complementary research, were collected to fulfil those aims. The study follows that customers generally prefer sourcing methods that are not harmful to the environment and do not support the exploitation of the workers. Moreover, most of them wouldn’t mind paying extra for coffee which meets their ethical requirements. Next, from the producers’ view, direct trade was found helpful among the researched farmers. Furthermore, it was discovered that certifications like Fairtrade can be beneficial in some cases, but their real benefits are questionable.